The Effect of Life Cycle Assessment on Performance Sustainability: The Moderating Roles of Bioaccounting and Smart Environmental - Ade Manggala Hardianto; Yuli Novitasari; Widianingsih Widyaningsih; Mutiara Sherly Amanah (Universitas Hayam Wuruk Perbanas, 2025)
The growing urgency to achieve long-term performance sustainability amidst dynamic environmental challenges presents a significant problem for modern organizations, particularly when life cycle management and ecological accountability are not optimally integrated. This study aims to analyze the effect of life cycle factors on performance sustainability while evaluating the dual moderating roles of bioaccounting and smart environmental in strengthening strategic responses to environmental and operational pressures. A quantitative approach was employed using survey data from corporate respondents, and the analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique to test indicator validity and structural relationships across variables. The findings indicate that life cycle significantly influences performance sustainability, and both bioaccounting and smart environmental function as effective moderators that enhance the alignment between corporate strategies and ecological responsibility. The implications of this research emphasize the importance of sustainability-oriented accounting innovation and environmentally intelligent decision-making as foundations for competitive advantage, regulatory compliance, and long-term value creation.